2021
DOI: 10.14704/nq.2021.19.6.nq21071
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Glaze Layer of Restorative Dental Zirconia by Adding Nano Alumina Ceramics

Abstract: The objective of this work is to study the effect of adding varying ratios of Nano Alumina to the glazing powder on glazing layer of restorative dental ceramic. The effect of addition is examined by applying Vickers hardness and surface roughness tests on the glazing layer. The specimens have been cut in a cubic form. The specimens were placed in the furnace for sintering up to temperature of 1450 oC. One specimen is glazed with glazing materials and the remaining three specimens are glazed with glazing materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The reason behind these results was the mechanical properties of glazing layer that enhanced by Alumina. The amount of alumina in the glaze materials according to the analysis done by energy-dispersive Xray analysis (EDAX) test, this agrees with (Moosa et al, 2021) Increased Alumina concentration will result in more crystal phases forming, raising the glazing layer's Vickers hardness number ‫و‬ which in turn affects zirconia's surface resistance and shortens the lifespan of artificial teeth (7). The explanation for the decreased microhardness results in Vita and Soprano brand glazing materials may be because the monolithic zirconia glaze groups were heated throughout the glazing process to the sintering temperature.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The reason behind these results was the mechanical properties of glazing layer that enhanced by Alumina. The amount of alumina in the glaze materials according to the analysis done by energy-dispersive Xray analysis (EDAX) test, this agrees with (Moosa et al, 2021) Increased Alumina concentration will result in more crystal phases forming, raising the glazing layer's Vickers hardness number ‫و‬ which in turn affects zirconia's surface resistance and shortens the lifespan of artificial teeth (7). The explanation for the decreased microhardness results in Vita and Soprano brand glazing materials may be because the monolithic zirconia glaze groups were heated throughout the glazing process to the sintering temperature.…”
Section: Discussionsupporting
confidence: 82%
“…In Table [5], Post Hoc Test (Bonferroni) shows a statistically significant difference between each two of the studied groups (VITA, Ivoclar, GC and Soprano) for hardness with p-value < 0.05, except for two, there no statistically significant association between (VITA & soprano) glaze and between (Ivoclar & GC) glaze with p-value > 0.05 for both. In Table [6], Energy-Dispersive X-Ray Analysis show the effect of the glazing materials on hardness will be related to one elemental composition Al weight % (7), which is used in this study. While the glazing material (powder) had more Aluminum (Al) in GC group than Ivoclar, VITA and Soprano.…”
Section: Resultmentioning
confidence: 99%
See 2 more Smart Citations
“…Venkatesh et al (91) added the nano-ZrO2 particles synthesized using the sol-gel method into the glaze at different rates and showed that the increase in the nano-ZrO2 content directly increased the wear resistance of the material. Moosa et al (92) applied a glaze containing nano-Al2O3 with 13nm particle size at different rates on zirconia restorations and determined that it was effective in increasing the resistance of the restoration.…”
Section: Use In Dental Glaze Materialsmentioning
confidence: 99%